Practice of Lange-Scale Commercial Engineering Deployment of IPv6 of Operator - Chenpeng Bai; We Guan (Dianxin kexue, 2013)
The IPv6 transition technologies were discussed and the guidelines were offered on how to select different transition technologies for network service provider base on the in-depth analysis of practical deployment of IPv6 on the IP network of Shaanxi Telecom.